Menerobos Pembelajaran Akidah Akhlak: Inovasi Kurikulum melalui Pendekatan In-Depth Learning di MTs Qurrota A’yun Bantul - Aliza Nur Azizah; Muh. Wasith Achadi (STKIP Subang, 2025)
This study aims to analyze the innovation of the in-depth learning curriculum in the teaching of faith and morals at MTs Qurrota A'yun. The research focuses on the background of the innovation, the curriculum model and design, planning, implementation, evaluation, and its advantages and limitations. This study used a qualitative approach with a case study through observation, documentation, and in-depth interviews with the principal, vice principal of curriculum, faith and morals teacher, and students. The data obtained were analyzed descriptively and analytically, linking it to theory and current research findings. The results indicate that the curriculum innovation emerged from collaboration between various parties committed to strengthening students' faith and morals. The learning design uses a mindful, meaningful, and joyful approach integrated with daily life. In planning and implementation, teachers undergo regular preparation and training, as well as provide mentoring to students. Evaluation is carried out continuously through daily journals (students' books) and observation of attitudes. The implementation of the in-depth learning approach has proven relevant and effective in developing contextual and adaptive faith and morals education in the global era. Keywords: Curriculum Innovation; In-Depth Learning; Akidah Akhlak.